2007
DOI: 10.1016/j.eurpsy.2007.10.010
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Online Game Addiction and Aggression, Self-Control and Narcissistic Personality Traits

Abstract: An interesting profile has emerged from the results of this study, suggesting that certain psychological characteristics such as aggression, self-control, and narcissistic personality traits may predispose some individuals to become addicted to online games. This result will deepen our understanding of the "at-risk" population for online game addiction and provide basic information that can contribute to developing a prevention program for people who are addicted to online games.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

31
412
10
33

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 594 publications
(513 citation statements)
references
References 35 publications
31
412
10
33
Order By: Relevance
“…However, statistical analyses that included potential mediating variables (the BAI, BDI, and CASS) showed that clinical factors played mediating roles only when aggression predicted IAD and not vice versa. Several studies regarding the relationship between Internet addiction and comorbid psychiatric disorders have been conducted, 21,43,44 enabling the current study to incorporate particular clinical variables (as measured by the BAI, BDI, and CASS) as potential mediators in this relationship. With respect to the influence of Internet addiction on aggression, it was found that Internet addiction predicted aggression in adolescents, irrespective of whether clinical factors were considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, statistical analyses that included potential mediating variables (the BAI, BDI, and CASS) showed that clinical factors played mediating roles only when aggression predicted IAD and not vice versa. Several studies regarding the relationship between Internet addiction and comorbid psychiatric disorders have been conducted, 21,43,44 enabling the current study to incorporate particular clinical variables (as measured by the BAI, BDI, and CASS) as potential mediators in this relationship. With respect to the influence of Internet addiction on aggression, it was found that Internet addiction predicted aggression in adolescents, irrespective of whether clinical factors were considered.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Lee and Shin [13] indicated possible associations between self-control and addictive consumption of avatars as a way of explaining this behavior. A recent study showed that self-control with aggression and narcissistic personality traits was negatively related to addiction to online games [14]. It is possible to predict that self-control can play an important role in Facebook addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Higher scores on neuroticism (Dong, Wang, Yang, & Zhou, 2012;Tsai et al, 2009), and low scores on extraversion (van der Aa et al, 2009;Xiuqin et al, 2010), agreeableness and emotional stability (van der Aa, et al, 2009) have been established as potentially important risk factors for Internet addiction. Internet gaming addiction specifically has been associated with neuroticism (Mehroof & Griffiths, 2010b;Peters & Malesky, 2008), aggression and hostility (Caplan, Williams, & Yee, 2009;Kim, Namkoong, Ku, & Kim, 2008;Mehroof & Griffiths, 2010a, 2010b, introversion (Caplan, et al, 2009), social inhibition (Porter, Starcevic, Berle, & Fenech, 2010), sensation-seeking (Mehroof & Griffiths, 2010a, 2010b, and diminished agreeableness (Peters & Malesky, 2008). In spite of the substantial evidence for the role of personality traits, far less is known about interactions between traits and specific uses of the Internet in increasing the risk of being addicted to the Internet.…”
Section: Introductionmentioning
confidence: 99%